Impact of climate change on the waters off southwest Taiwan: predicted alterations in moonfish distribution and catch rates - Ray, Aratrika; Mondal, Sandipan; Lee, Ming-An; Lu, Quang-Huy; Sihombing, Riah Irawati; Wang, Yi-Chen (Frontiers in Marine Science, 2025)
IntroductionPrior research emphasizes the beneficiaries and detractors in fisheries due to climate change, focusing on alterations in biomass, species mix, and potential yields. Comprehending the potential impact of climate change on the fisheries income of maritime nations is an essential subsequent step in formulating effective socio-economic policies and food sustainability plans to mitigate and adapt to climate change. Globally, our understanding of small-scale fisheries remains inadequate, despite their significance for food security and livelihoods.MethodsThis study demonstrates by using global circulation model (GCM: IPSL) that moonfish catches react favorably to climate alterations in southwest Taiwan, through the analysis of primary fishery data from 2014-2020 spanning two seasons – northeast and southwest monsoons by using generalized additive models. The anticipated habitat shifts were utilized to examine the impact of future environmental changes on moonfish catch rates.ResultBy the 2060s, moonfish emerged as a winner of climate change in this study region. The habitats of moonfish are projected to shift westward during southwest monsoon, with a mean habitat centroid displacement of about 50-150 Km between RCP 2.6 and 8.5 during NE monsoon while 20-40 Km during the SW monsoon. A possible explanation could be that the Taiwan Strait (TS) may serve as a geographical barrier to the northward migration of south-dwelling moonfish. The study further demonstrates that moonfish fisheries catch rates may increase by 22.5% and 17.2% beyond the present catch rates by the 2060s under elevated CO2 emission scenarios during northeast and southwest monsoons respectively.DiscussionOur findings indicate the necessity for comprehensive economic evaluations regarding the potential impacts of climate change on regional small-scale marine fisheries, contributing to the adaptive conservation and management of fish habitats.